Authenticity in Language Testing - Zheng, Yujing; Iseni, Arburim (ANGLISTICUM. Journal of the Association-Institute for English Language and American Studies, 2017)
Since the communicative language testing was proposed in 1980s, authenticity, as a distinctive feature of it, has been a heated topic in modern language testing. This paper conducts a brief analysis of the concept of authenticity in language testing, and investigates such two characteristics of it as subjectiveness and relativity. It also comments on the authenticity in scoring. The authors hold that authenticity is a relative concept and should be considered to achieve appropriate balance with the other qualities (i.e. reliability, construct validity, interactiveness, impact, practicality) of language testing. Keywords: authenticity, subjectiveness, relativity.